Exames citopatológicos do colo do útero realizados no sistema único de saúde, em um município de tríplice fronteira no Paraná - Turkiewicz, Mauricio (2023)
Cervical cancer is caused by persistent infection with oncogenic human papillomavirus and evolves slowly from precursor lesions. Periodic performance of high-quality cytopathological examinations is the way used worldwide in the screening of this cancer, however, care for people with cancer was suspended during the COVID19 pandemic giving priority to urgencies and emergencies in health units. The objective of this project was to evaluate the cytopathological exams of the cervix performed in the Unified Health System, in a triple border municipality in Paraná, in the period before and during the COVID-19 pandemic. The quantitative and retrospective study was used as a method based on the cancer information system and the results of 106,029 cytopathological exams of the cervix performed by primary health care from January 2014 to October 2021, in the municipality of Foz do Iguaçu-Paraná. By analyzing the quality indicators, the following variables: rejected, satisfactory and unsatisfactory exams for oncotic analysis; squamocolumnar junction and altered cytopathological results. Data analysis was carried out using the Microsoft Office Excel program (97- 2003), and the quality indices were evaluated by calculating the Internal Quality Monitoring indicators. Among the main results obtained, it was verified that the percentage of rejection in this work (0.37%) was above the standard considered by the Ministry of Health, up to 0.1%. In the analytical phase, 99.03% of the samples were satisfactory for oncotic analysis, and 0.60% were unsatisfactory, a percentage within the parameters recommended by the Ministry of Health (up to 5% for unsatisfactory). The number of cytopathological exams analyzed in the first year of the pandemic reduced considerably, approximately 40%. In Brazil, in 2019-2020, there was a 42% reduction in cytopathological tests, a percentage very close to this study. The squamocolumnar junction ranged from 36.5% to 89.3%, and the total number of exams with altered results was 3,377, with a variation in the positivity rate of more than six and a half times, from 1.0% to 6.5%, and the percentage of high-grade lesions varied six times, from 0.2% to 1.2%. The HSIL indicator represents the number of truly precursor lesions, being the main objective of secondary prevention of this cancer, due to its potential for progression. In conclusion, during the pandemic period evaluated, a greater number of altered cytopathological exams and a preponderance of in situ and invasive carcinomas and adenocarcinomas were observed. These data can help local managers in strategies for adequate monitoring and treatment of these women with precursor lesions and/or cervical cancer